2001
DOI: 10.1021/np010010t
|View full text |Cite
|
Sign up to set email alerts
|

Withanolides from Salpichroa origanifolia

Abstract: Five new withanolides, 5 alpha,6 alpha:22,26:24,25-triepoxy-16 alpha,26-dihydroxy-18(13-->17)-abeo-ergosta-2,13-dien-1-one (salpichrolide N, 1), 5 alpha,6 alpha:22,26:24,25-triepoxi-15 alpha,26-dihydroxyergosta-2,16-dien-1-one (salpichrolide L, 2), 5 alpha,6 alpha:22,26-diepoxi-24,25,26-trihydroxy-17(13-->18)-abeo-ergosta-2,13,15,17-tetraen-1-one (salpichrolide M, 3a), 5 alpha,6 alpha:22,25:22,26-triepoxy-24-hydroxy-17(13-->18)-abeo-ergosta-2,13,15,17-tetraen-1-one (salpichrolide J, 4), and 5 alpha,6 alpha:22,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…On the other hand, a higher variability was observed for the side chain. Salpichrolides H (343) and I (344) were isolated from plants collected in Buenos Aires in the winter (158), and salpichrolides J (345), K (346), and M (347) from plants collected in Salta province (Argentina) in the summer (159). Salpichrolides H (343) and M (347) correspond to the two possible products resulting from hydrolytic (trans) cleavage of the sidechain epoxide.…”
Section: Aromatic Ring-d Withanolides and Related Steroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a higher variability was observed for the side chain. Salpichrolides H (343) and I (344) were isolated from plants collected in Buenos Aires in the winter (158), and salpichrolides J (345), K (346), and M (347) from plants collected in Salta province (Argentina) in the summer (159). Salpichrolides H (343) and M (347) correspond to the two possible products resulting from hydrolytic (trans) cleavage of the sidechain epoxide.…”
Section: Aromatic Ring-d Withanolides and Related Steroidsmentioning
confidence: 99%
“…Besides the withanolides with an aromatic D ring, salpichrolides D (350), (157) L (351), and N (352) (159), with a normal (5-membered) D ring were isolated from S. origanifolia. All of these have a characteristic 5a,6a-epoxide moiety, unique to S. origanifolia.…”
Section: Aromatic Ring-d Withanolides and Related Steroidsmentioning
confidence: 99%
“…Increasing the p electron conjugated system leads to p ? p* at the lower energy state and redshifting of k max (224-320 nm) as in withanolides with aromatic rings (Tettamanzi et al 2001) and a 2,4-diene-1-oxo in skeleton structure (Pérez-Castorena et al 2006). Versus the characteristic absorption (225 nm) of the usual dimethyl-substituted a, bunsaturated d-lactone in withanolides, the large substituent groups will break down the conjugated system and result in k max blueshifting from 215 to 224 nm, e.g., withanolides with a 27a-hydroxymethyl (Khan et al 1999a, b;Liu et al 2006).…”
Section: Spectral Generalization Of Withanolidesmentioning
confidence: 97%
“…It is particularly worth mentioning that in (Minguzzi et al 2002). Consulting the literature from 1996 to 2014 revealed that most compounds are 22R-configuration with only 5 compounds having a 22S-configuration (Jaborosalactone 7 , Salpichrolide J (Tettamanzi et al 2001), Glucosomniferanolide (Kumar et al 2004), Jaborosalactone 43, 179). This demonstrates that 22R-withanolides are the preferred conformation and constitute a large fraction of natural withanolides.…”
Section: Absolute-configurationmentioning
confidence: 99%
“…Withanolides are a group of C‐28 steroidal lactones and lactols isolated from several genera of the Solanaceae family . A small group of these compounds, termed salpichrolides, were isolated from Salpichroa origanifolia and exhibited antiestrogenic effects . Salpichrolides such as Salpichrolide A (Fig.…”
Section: Introductionmentioning
confidence: 99%